A salicylic acid-induced lectin-like protein plays a positive role in the effector-triggered immunity response of arabidopsis thaliana to pseudomonas syringae Avr-Rpm1 - Armijo, Grace (2013)
Salicylic acid (SA) is one of the key hormones that orchestrate the pathogen-induced immune response in plants. This response is often characterized by the activation of a local hypersensitive reaction involving programmed cell death, which constrains proliferation of biotrophic pathogens. Here, we report the identification and functional characterization of an SA-induced legume lectin-like protein 1 (SAILLP1), which is coded by a gene that belongs to the group of early SA-activated Arabidopsis genes. SAI-LLP1 expression is induced upon inoculation with avirulent strains of Pseudomonas syringae pv. tomato via an SA-dependent mechanism. Constitutive expression of SAI-LLP1 restrains proliferation of P. syringae pv. tomato Avr-Rpm1 and triggers more cell death in inoculated leaves. Cellular and biochemical evidence indicates that SAI-LLP1 is a glycoprotein located primarily at the apoplastic side of the plasma membrane. This work indicates that SAI-LLP1 is involved in resistance to P. syringae pv. tomato Avr-Rpm 1 in Arabidopsis, as a component of the SA-mediated defense processes associated with the effector-triggered immunity response.